2021
DOI: 10.3390/microorganisms9071389
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Portrayed against HIV: Contrary Viral Strategies in Similar Disguise

Abstract: SARS-CoV-2 and HIV are zoonotic viruses that rapidly reached pandemic scale, causing global losses and fear. The COVID-19 and AIDS pandemics ignited massive efforts worldwide to develop antiviral strategies and characterize viral architectures, biological and immunological properties, and clinical outcomes. Although both viruses have a comparable appearance as enveloped viruses with positive-stranded RNA and envelope spikes mediating cellular entry, the entry process, downstream biological and immunological pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 660 publications
(648 reference statements)
0
4
0
Order By: Relevance
“…38 Some variants like B.1.1.7 (alpha), B.1.351 (beta), P.1 (gamma), and B.1.617.2 (delta), which were first found in the United Kingdom, South Africa, Brazil, and India, respectively, were designated as variants of concern (VOC) by WHO. [39][40][41] To evaluate the effect of pep39 on the VOCs, we performed almost 2 μs long MD simulations and MMGBSA calculation. Pep39 stays bound with all VOCs for the entire length of the simulation with significant binding affinity (Table 2).…”
Section: Binding Of Pep39 To Variants Of the Spike Proteinmentioning
confidence: 99%
“…38 Some variants like B.1.1.7 (alpha), B.1.351 (beta), P.1 (gamma), and B.1.617.2 (delta), which were first found in the United Kingdom, South Africa, Brazil, and India, respectively, were designated as variants of concern (VOC) by WHO. [39][40][41] To evaluate the effect of pep39 on the VOCs, we performed almost 2 μs long MD simulations and MMGBSA calculation. Pep39 stays bound with all VOCs for the entire length of the simulation with significant binding affinity (Table 2).…”
Section: Binding Of Pep39 To Variants Of the Spike Proteinmentioning
confidence: 99%
“…Interestingly, SARS-CoV-2 and HIV-1 do share similarities [ 7 , 8 ]. Indeed, despite engaging different entry receptors, target cells, and transcription and downstream processes, HIV-1 and SARS-CoV-2 follow similar principles of class-I-glycoprotein-mediated viral fusion and entry.…”
Section: Invasion Of the Vagus Nerve By Pathogens Appears As A Common...mentioning
confidence: 99%
“…As SARS-CoV-2 has 2–3 times more spike proteins per virus than HIV-1 [ 8 ], and as the vagally supplied entrance organs are more numerous in COVID-19 than in AIDS (nose, mouth, lungs, and guts versus urogenital tract, respectively), the invasion of the vagus nerve by SARS-CoV-2 is likely to be more extensive in COVID-19. Adverse outcomes (e.g., death) may not come from the infection itself, but may depend on the importance of vagus nerve invasion and subsequent incapacitation to restore homeostasis.…”
Section: Invasion Of the Vagus Nerve By Pathogens Appears As A Common...mentioning
confidence: 99%
“…Although striking differences exist in the biology of SARS-CoV-2 and HIV, their proteins for cell attachment share common features. Both the SARS-CoV-2 spike and HIV envelope (Env) are class 1 fusion machineries, require furin cleavage to generate their surface (S1/gp120) and transmembrane (S2/gp41) subunits, and are heavily glycosylated [ 25 ]. Based on these structural similarities, several authors proposed SARS-CoV-2 spike/HIV Env cross-reactive Abs as an explanation for the observed false-reactive HIV screening tests post SARS-CoV-2 infection [ 15 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%